Analysis of auditor`s reports and bankruptcy risk in banking sector in the Republic of Serbia - Milovan Stanisic; Danka Stefanovic; Nada Arezina; Vule Mizdrakovic (Amfiteatru Economic)
This paper aims to point out the significance of external audit and auditor’s reports. The stability of banks and its operations are vital not only for efficient financial system functioning, but also for overall industry. The banking sector, both in developed and undeveloped countries, experienced financial crisis in the last few years. Considering these circumstances and the fact that demands of financial statements users grow in complexity, their control is essential. We provide the empirical evidence on the banking sector auditor’s reports in the Republic of Serbia, with particular reference to auditor’s opinions and audit agencies that had conducted banks audits. The review of the audit legislation and professional standards will be presented, as well as the notion of bankruptcy risk and its relevance for baking sector. Our research results indicate that special attention should be paid to banks which auditor’s report had some explanatory paragraphs or even qualification. In conclusion we highlight the red flags that may damage banks operations and emphasize the importance of keeping the high level of auditor’s independence with the intention to provide confidence to stakeholders who form their decisions based on their reports.